Assessment of Land Use Land Cover with Special Reference to Trees Outside Forests (TOF) in The Central Region of Kashmir Himalayas Using IRS LISS-IV data - Mehraj, Basira; Wani, Akhlaq Amin; Gatoo, Aasif Ali; Saleem, Ishrat; Anjum, Afshan; Arjumand, Tahera; Hussain, Arshy; Murtaza, Shah; Farooq, Amir; Islam, M. A. (Indian Forester, 2021)
Spatial assessment of trees outside forests (TOFs) is widely being accepted as a critical matter in sustainable natural resource management owing to their role in providing variety of goods and valuable services like carbon sequestration. Such information is highly important for decision making in projects under CDM and REDD+. The present study was taken to assess landuse land cover (LULC) with special reference to TOF in central region of Kashmir Himalayas using high spatial resolution IRS-LISS IV data of 2016. LULC classes delineated were supplemented with validation through ground truthing. The results revealed that forest class occupied maximum area (34.43%) of the region. Overall classification accuracy of LULC map estimated as 85.00% (kappa coefficient of 0.833). TOFs were classified into three strata i.e. block, linear and scattered as per FSI scheme of classification of TOF (rural) followed in India. Based on the preliminary survey results, TOF strata were further classified into six TOF practices. Among the TOF practices roadside plantations, riverside plantations and boundary plantations) formed linear stratum while as woodlots & horticulture formed block stratum and the last scattered patches with clumpy plantation (SPCP) was included in scattered TOF stratum. Area under TOF was found to be 6.77% of total geographical area. Among TOF strata, block TOF covered the maximum area (6.395%) whereas linear TOF occupied 0.370% and scattered TOF occupying 0.005%. Among the TOF practices, horticulture covered the maximum area of 5.73% whereas SPCP occupied only 0.01% of the region. The overall classification accuracy of TOF map was assessed to be 86.11% with kappa coefficient of 0.833. There is a need to assess TOFs on periodical basis in the region for temporal changes as TOFs assume importance in provisional and regulating ecosystem services like prevention of soil erosion and climate amelioration.